2002
DOI: 10.1038/sj.gt.3301654
|View full text |Cite
|
Sign up to set email alerts
|

LCR-mediated, long-term tissue-specific gene expression within replicating episomal plasmid and cosmid vectors

Abstract: Locus control regions (LCRs)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
2

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 45 publications
(68 reference statements)
1
20
0
2
Order By: Relevance
“…16,36,37 The average copy number of the vector in K562 cells was estimated to be low, similar to previously published reports of pEPI copy number in HeLa and CHO cells, 16,18,36 as well as of that of EBV-based episomes in K562 cells. 24 This is in accordance with a tightly regulated once-per cell cycle replication of pEPI vector. 36 Thus, pEPI-eGFP can be a valuable tool in basic research as an expression vector conferring sustained and regulated expression of transgenes, being easy and simple to use as a nonviral gene transfer system.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…16,36,37 The average copy number of the vector in K562 cells was estimated to be low, similar to previously published reports of pEPI copy number in HeLa and CHO cells, 16,18,36 as well as of that of EBV-based episomes in K562 cells. 24 This is in accordance with a tightly regulated once-per cell cycle replication of pEPI vector. 36 Thus, pEPI-eGFP can be a valuable tool in basic research as an expression vector conferring sustained and regulated expression of transgenes, being easy and simple to use as a nonviral gene transfer system.…”
Section: Discussionsupporting
confidence: 76%
“…BamHI-digested total DNA from stably transfected K562 cells was Southern blotted and probed simultaneously with a pEPI-eGFP-specific probe, as above, and a probe specific for the endogenous b-globin gene. By comparing the intensities of the bands corresponding to the two probes and considering b-globin band intensity as a three-copy gene reference (since K562 cells are trisomic for chromosome 11 and therefore possess three copies of the b-globin gene), 21,24 we estimated the average copy number of the vector in K562 cells to be 2.5 ( Figure 1e). The plasmid band generated on Southern blots of MEL cells at various time points did not exhibit a decrease in intensity (Figure 1b), suggesting that plasmid loss could not account for the decline in eGFP expression.…”
Section: Pepi-egfp Functions As a Stable Episome In Hematopoietic Promentioning
confidence: 99%
“…LCR elements have been used in a number of studies with the aim of enhancing and prolonging transgene expression. A combination of HS 2, 3 and 4 from the globin LCR was shown to endow an episomal plasmid vector with the ability to maintain stable transgene expression in the absence of drug selection for 60 days (more than 60 cell replications) [Chow et al, 2002]. Miao et al [Miao et al, 2000;Miao et al, 2001] also incorporated the apolipoprotein E LCR into episomal plasmid vectors and showed significant improvement over constructs lacking the LCR.…”
Section: Locus Control Regions (Lcrs)mentioning
confidence: 99%
“…The inclusion of bLCR minilocus in the cosmid construct prevented transgene silencing over time. 126 Satoh et al 81 reported successful transfer and expression of human ADA gene in human hematopoietic progenitor cells with colony-forming capacity within an EBV-based vector.…”
Section: 78mentioning
confidence: 99%